Faktor-Faktor Keberhasilan Perkumpulan Petani Pemakai Air (P3A) pada Program (P3-TGAI) di Kabupaten Solok - Zuherlan, Zuherlan; Zaitul, Zaitul; Mizwar, Zuherna (Universitas Batanghari, 2025)
Solok Regency, West Sumatera is one of the main rice-producing regions in West Sumatra, with a paddy field agricultural system that heavily relies on irrigation networks. This condition makes Solok Regency a strategic area for implementing the P3-TGAI Program (Irrigation Water User Association Empowerment – Irrigation Smallholder Farming Support Program). This study aims to identify, validate, and develop a model of the success factors of the P3A (Irrigation Water User Associations) in implementing the P3-TGAI program in Solok Regency. A mixed-methods approach combining quantitative and qualitative techniques was used, involving a survey of 99 respondents across 5 key factors (22 variables) in the research instrument. The data were tested for validity, reliability, and factor analysis. This study also employed the Partial Least Squares (PLS) approach as the data analysis method. PLS is a technique within Structural Equation Modeling (SEM) that is component- or variance-based, where the factors were evaluated using Measurement Model Analysis (MMA). The analysis was conducted using SPSS and Smart PLS software, through the assessment of convergent validity and discriminant validity. The results of the study revealed four factors that directly influence the success of P3A in Solok Regency: Program Communication, Labor, Materials, and Community Participation. The dominant factor influencing success was Community Participation, with a path coefficient of 0.863.